AN INVESTIGATION ON THE IMPACT OF TEMPERATURE AND THICKNESS VARIATION ON THE PERFORMANCE OF CuAlO2/ZnO AND NiO/ZnO PEROVSKITE SOLAR CELL: A NUMERICAL SIMULATION APPROACH - Tukur Mohammed, Aminu; Darma Hassan, Tijjani; Aujara Musa, Kabiru (FUDMA Journal of Sciences, 2025)
This study presents a numerical simulation of CuAlO2/ZnO, and NiO/ZnO perovskite solar cells (PSCs) using SCAPS-1D software focussing on the impact of temperature variation (300-400K) and layer thickness optimization (50-140nm, varied in 10nm intervals) on device performance. The investigation evaluates key photovoltaic parameters including open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF), and power conversion efficiency (PCE) to determine the optimal design configurations for improved efficiency. The result reveals that, for the CuAlO2/ZnO, increasing the operating temperature leads to a gradual decline in Voc, from 1.05 to 0.91V, while Jsc increased slightly from 23.1mA/cm2 to 25.4mA/cm2. However, FF dropped from 78% to 68% and PCE declined from 18% at 300K to 13.5% at 400K due to enhanced carrier recombination and decreased built in potential. The device optimal performance was obtained at a CuAlO2 thickness of 90nm and ZnO thickness of 100nm achieving Voc=1.05V, Jsc=23.8mA/cm2, FF=78% and PCE=18.6%. In contrast, for the NiO/ZnO configuration Voc reduces from 1.02V at 300K to 0.89V at 400K, while Jsc slightly increased from 24.3mA/cm2 to 26.1mA/cm2 and FF fell from 76% to 66% leading to PCE drop from 18.9% to 14.2%. Layer thickness strongly influences light absorption and charge transport. The NiO/ZnO device showed its optimum performance with a NiO and ZnO layer thicknesses of 100 and 110nm respectively, producing Voc=1.02V, Jsc=24.3mA/cm2, FF=76% and PCE=18.9%.